2016
DOI: 10.1007/s13224-016-0869-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Misoprostol Only and Mifepristone Plus Misoprostol in Second Trimester Termination of Pregnancy

Abstract: Objective To compare the effectiveness, success rate and induction to abortion interval between administration of misoprostol only and mifepristone with misoprostol in second trimester abortions (14-20 weeks). Materials and methods The study was conducted by dividing women approaching for second trimester termination, into two groups each consisting of 100 women.Group-I received only misoprostol; 600 mcg initial vaginal insertion followed by 400 mcg sublingually every 3 h until termination. Women in Group-II r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…In a study conducted by Prasanna Lekha Akkenapally (2016) 3 , the mean dose of misoprostol required in group A was 1046mcg while that required in Group B was 1610mcg with a p value being less than 0.001 which was statistically significant.…”
Section: Dose Of Misoprostolmentioning
confidence: 90%
See 3 more Smart Citations
“…In a study conducted by Prasanna Lekha Akkenapally (2016) 3 , the mean dose of misoprostol required in group A was 1046mcg while that required in Group B was 1610mcg with a p value being less than 0.001 which was statistically significant.…”
Section: Dose Of Misoprostolmentioning
confidence: 90%
“…In a study by Prasanna Latha Akkenapally 3 , the mean blood loss in group A was less (mean blood loss 52.55ml) as compared to Group B (mean blood loss 97.20ml).…”
Section: Amount Of Blood Loss and Requirement Of A Blood Transfusionmentioning
confidence: 95%
See 2 more Smart Citations
“…Original clinical trials [21,22] and reviews [23][24][25] showed that the combination regimen of mifepristone and misoprostol has resulted in higher proportion of success rate as compared to the misoprostol alone in second trimester abortions. On the other hand, a systematic review conducted to determine the effects of mifepristone during third trimester cervical ripening concluded to have inadequate evidence for suggesting the drug for labour induction [26].…”
Section: Introductionmentioning
confidence: 99%